BluePhone push-to-talk VOIP on Bluetooth-enabled mobile phones - Arce, Ralph Justin
Voice over IP (or VoIP) is rapidly becoming a strong competitor in the communication area. Its rates are getting cheaper and cheaper, and consumers are starting to look at the service as an alternative to costly calls (e.g., long distance, NDD, etc). However, to be able to deploy VoIP for use, one is required to have a broadband connection available. For consumers who are already subscribed to a broadband Internet service, the costs may seem redundant, as they have to pay for both the broadband connection and the VoIP service. In this research, we intend to create a structured VoIP streaming system for Bluetooth-enabled mobile devices. This project aims to realize the potential of mobile phones as a streaming device. This project aims to realize the potential of mobile phones as a streaming device. This project aims to realize the potential of mobile phones as a streaming device. Target platforms will be Java Runtime-equipped and Bluetooth-enabled mobile phones that do not have any other means of communicating with the Internet other than Wireless Application Protocol (WAP), although any Java Runtime-equipped mobile devices could be supported too. This is because Bluetooth phones are a standard nowadays, and we would like to harness its other potentials (other than the basic file sharing profile). The research would include building a software gateway that connects Bluetooth and IP networks, creating a proxy server that would communicate with the IP network in place of the mobile client, and voice exchange through Bluetooth.